Novel Approaches in Landslide Monitoring and Data Analysis - Blahut, Jan; Jaboyedoff, Michel; Thiebes, Benni (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Significant progress has been made in the last few years that has expanded the knowledge of landslide processes. It is, therefore, necessary to summarize, share and disseminate the latest knowledge and expertise. This Special Issue brings together novel research focused on landslide monitoring, modelling and data analysis.